The Relationship between Quick Of Blood and Fatigue in Stage V Chronic Renal Failure Patients Undergoing Hemodialysis - Nanda Nadzim Ahmad Nanda; Danny Putri Sulistyaningrum; Riris Risca Megawati (HealthCare Nursing Journal, 2023)
Chronic kidney failure is one of the non-communicable diseases, where the disease process takes a long time so that kidney function cannot return to its original state. Quick of blood should be <200 mL/minute in Indonesian people because if the QB rotation is too fast it can cause nausea, dizziness and rupture of the vein Regarding its relationship with the incidence of fatigue level itself, there has not been much research. However, giving very high Quick of Blood will have an impact on intra and post hemodialysis complications. The purpose of this study was to determine the relationship between quick blood and fatigue in stage V chronic kidney failure patients after undergoing hemodialysis. The design of this study used quantitative research with descriptive analytic, namely cross sectional. The number of samples in this study were 62 respondents with a purposive sampling data collection technique. Measuring tool used FACIT Scale. The Spearman Rank statistical test on the correlation and regression test of the quick of blood relationship with fatigue shows a weak relationship (r = 0.001) and has a negative pattern, the lower the quick of blood, the more fatigue increases. Statistical test results obtained (p = 0.992) (Ho accepted and Ha rejected). In this study there was no significant relationship between quick of blood and fatigue. The results of this study are expected to increase insight and knowledge in the field of patient care to reduce fatigue in hemodialysis action.